Changes of explosive strength in professional basketball players after a six week training cycle with plyometric training and resistance training - Michal Lehnert; Karel Hůlka; Ladislav Toth; Tomáš Malý (Palacký University Olomouc, 2014)
BACKGROUND: Explosive strength of the lower extremities and agility are important parts of game performance in basketball. Although numerous studies have focused on the assessment of the training eﬀect of plyometric training, studies focusing on elite players are missing. OBJECTIVE: The aim of the study was to find out what changes in explosive strength of the lower extremities take place after a 6 week strength training with plyometric exercises and resistance exercises in elite basketball players. METHODS: Elite basketball players (n = 12; age 24.71 ± 1.5 years; height 197.0 ± 7.6 cm; weight 95.8 ± 8.1 kg) performed during pre-season a 6 week training program with plyometric exercises and resistance exercises which were conducted biweekly during the pre-season. The changes in explosive strength were measured by the squat jump without arms, the counter movement jump without arms, the counter movement jump free arms and the 2 step run up jump. The players participated in two measurements. The 1st (pretesting) was performed on the first day of pre-season and the 2nd (posttesting) was completed two days after terminating the PT programme. The diﬀerences between the average values of the monitored parameters were determined by the Wilcoxon paired test. To calculate the eﬀect size formula according to Fritz, Morris, and Richler (2012): R = Z/√N was used. RESULTS: Analysis of intra-group changes confirmed significant diﬀerences between the two measurements in tests of vertical jump squat (Z = 2.58, p = .01, r = .75), vertical jump from the point of the swing arm (Z = 2.49, p = .01, r = .72) and vertical jump from place without the swing arm (Z = 2.75, p = .01, r = .79). In case of the two step run up jump significant diﬀerences were not found (Z = 1.60, p = .11, r = .56). Analysis of intra-individual changes showed the significant interindividual diﬀerences in the changes of the explosive power of the lower limbs after a 6 week training. The improvement in all tests was observed in nine of the twelve players, oppositelly the deterioration in one player. CONCLUSIONS: The results of the study in elite basketball players have confirmed that the inclusion of plyometric exercises and exercises with additional resistance in the preparatory period may lead to significant changes in explosive power even elite senior basketball players.